Analisis Kadar Tanin dalam Ekstrak Daun Mimba (Azadirachta indica a. Juss) dengan Pelarut Air dan Etanol - Mihra, Mihra; Jura, Minarni Rama; Ningsih, Purnama (Universitas Tadulako, 2018)
Neem plant is a widely used in agriculture as green fertilizer, pesticides and insecticides. People usually use the leaves as for lowering blood sugar, skin diseases, preventing infection, and reducing itching. This study aims to identify and determine tannins levels containing in neem leaves extracts. This study applied extraction by maceration method using 2 different solvents, water and ethanol. Tannin is a metabolite secondary compound belong to phenolic compound groups which oxidized easily by strong oxidization agent (potassium permanganate) so then its determination utilized permanganate method (Lowenthal-Procter). The results showed that neem leaves in 250 mL water solvent contains 0.55% of tannin, while in 250 mL ethanol solvent and concentration of 96% contains 0.27% of tannin.Â